2021
DOI: 10.21037/atm-21-1166
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of plaque and brain imaging biomarkers for stroke risk stratification in patients with atherosclerotic carotid artery disease

Abstract: In this narrative review, we aim to review imaging biomarkers that carry the potential to noninvasively guide stroke risk stratification for treatment optimization.Background: Carotid atherosclerosis plays a fundamental part in the occurrence of ischemic stroke.International guidelines select the optimal treatment strategy still mainly based on the presence of clinical symptoms and the degree of stenosis for stroke prevention in patients with atherosclerotic carotid plaques. These guidelines, based on randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Recurrent strokes tend to be more severe and have a worse prognosis than primary strokes, Early identification of patients at high risk of recurrent stroke is important. In previous studies, intracranial atherosclerotic plaque (ICAP) features based on HR-VWI, including positive remodeling, intraplaque hemorrhage, and plaque enhancement, have been shown to be correlated with the recurrence of stroke (10)(11)(12)(13)(14), although conclusions regarding the specific correlations have remained controversial. The characteristics of intracranial arterial culprit plaques based on HR-VWI can provide a basis for differential diagnosis of clinical subtypes of sICAS patients and stratification of risk of stroke recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent strokes tend to be more severe and have a worse prognosis than primary strokes, Early identification of patients at high risk of recurrent stroke is important. In previous studies, intracranial atherosclerotic plaque (ICAP) features based on HR-VWI, including positive remodeling, intraplaque hemorrhage, and plaque enhancement, have been shown to be correlated with the recurrence of stroke (10)(11)(12)(13)(14), although conclusions regarding the specific correlations have remained controversial. The characteristics of intracranial arterial culprit plaques based on HR-VWI can provide a basis for differential diagnosis of clinical subtypes of sICAS patients and stratification of risk of stroke recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings may help elucidate the clinical events and outcomes in anterior and posterior circulation stroke. Plaque hypo-intensity in ICAS serves as an imaging biomarker of intraplaque lipid core, and plaque contrast enhancement as intraplaque inflammation and neovascularization [19,20]. Both plaque imaging features provide potential clues to vulnerable plaques at high risk for rupture and future vascular ischemia [20,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement index (EI) was calculated as follows: EI = ([SI plaque / SI gray matter on post-contrast T1w images] -[SI plaque /SI gray matter on precontrast T1w images])/(SI plaque /SI gray matter on pre-contrast T1w images) × 100% [11]. Plaque contrast enhancement was shown in strong association with intraplaque inflammation and neovascularization [20]. Vessels with stenotic degrees over 30% on HR-VWI were identified on the matched TOF-MRA and visually classified into normal, irregular (undulating lesion surface lining), stenotic, and occluded [21].…”
Section: Study Subjectsmentioning
confidence: 99%
“…The use of carotid plaque hypo-echogenicity as a risk stratification biomarker for predicting the annual risk for cerebrovascular ischemic events (stroke, TIA, amaurosis fugax) is supported by histopathologic studies showing that echolucent plaques mostly consist of lipid-rich necrotic cores (and/or) and intraplaque hemorrhage [ 15 ]. A meta-analysis involving 7557 asymptomatic patients followed for more than 3 years, demonstrated that plaques described as echolucent, showing intraplaque neovascularization and ulceration were associated with twice the risk of ischemic symptoms compared to stable echogenic plaques [ 16 ].…”
Section: Plaque Echogenicitymentioning
confidence: 99%